The Right of Inquiry of The House of Representatives in the Constitutional System: Between The Supervisory Function and The Potential for Abuse - Humah, Darsis (Jurnal Hukum dan Keadilan, 2025)
The right of inquiry is one of the constitutional rights of the House of Representatives as regulated in Article 20A paragraph (2) of the 1945 Constitution and the MD3 Law as an instrument of supervision over the government. After the amendment of the 1945 Constitution, the position of the House of Representatives has been strengthened as an important actor in the checks and balances mechanism. However, in practice, the use of the right of inquiry often raises debate, both as a form of constitutional supervision and as a political bargaining tool that has the potential to be abused. This article aims to analyze the position of the DPR's right of inquiry in the Indonesian constitutional system, identify its function and relevance to democracy, and examine its potential abuse in contemporary political practice. This research uses  a normative juridical  approach with a qualitative analysis method through literature review, laws and regulations, Constitutional Court decisions, and SINTA and Scopus indexed scientific publications for the 2020–2025 period. The results of the study show that normatively, the right of inquiry has a strong and relevant legal basis to strengthen the principles of accountability and transparency of governance. However, regulatory weaknesses, especially related to the follow-up of investigation results, make the effectiveness of the right of inquiry often limited. In addition, the dominance of the political majority in parliament and the tendency to politicize make the right of inquiry more often used as a political instrument than as an instrument of substantive supervision. In conclusion, the urgency of strengthening the right to inquiry lies in regulatory reform, strengthening the ethical mechanism of the House of Representatives, and increasing civil society participation, so that this right truly functions as a democratic instrument to prevent abuse of power